The Novel-miR-659/SPP1 Interaction Regulates Fat Deposition in Castrated Male Pigs - Lianmei Xiao (Animals, 2022)
Castration is usually used to remove boar taint in commercial pork production, but the adipose accumulation was increased excessively, which affected the meat quality of pigs. Based on our previous study, secreted phosphoprotein 1 (SPP1) was significantly differentially expressed between castrated and intact male pigs. However, the role of SPP1 in regulating adipose growth and fat storage caused by castration is unknown. In this study, SPP1 was identified to inhibit adipogenesis by the expression of adipogenic markers PPARγ and FABP4 as well as Oil red staining assay during differentiation of porcine bone marrow mesenchymal stem cells (pBMSCs). Subsequently, testosterone was used to treat pBMSCs to simulate the androgen status of intact pigs. Compared with the control groups without testosterone, the SPP1 expression in the testosterone group was markedly increased in the late stage of pBMSCs differentiation. Furthermore, novel-miR-659 was predicted by TargetScan and miRDB to target SPP1 and verified through a dual-luciferase reporter assay. Oil Red O staining assay indicated that novel-miR-659 overexpression significantly promoted adipogenesis, whereas novel-miR-659 inhibition suppressed adipogenesis. The expressions of adipogenic markers PPARγ and FABP4 showed the same tendency. Taken together, our study found that the targeted interaction between novel-miR-659 and SPP1 is involved in regulation of fat deposition in castrated male pigs.